Faktor yang Berpengaruh dengan Kejadian Hipertensi pada Usia 20-54 Tahun di Wilayah Kerja Puskesmas Wae Nakeng - Pascalita Nggalanai Tanggu; Sigit Purnawan; Indriati A.Tedju Hinga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
The World Health Organization (2018) shows that about 1.13 billion people in the world have hypertension, and it is estimated that by 2025 there will be 1.5 billion people affected by hypertension. Hypertension cases at the Wae Nakeng Health Center in 2021 were 483 cases and increased in 2022 by 582 cases. Hypertensive visits in the age group of 20–54 years at the Wae Nakeng health center in 2022 were high, amounting to 1,184 visits. This study was observational-analytic using a case-control research design. Sampling in this study was divided into two groups, namely the case group using simple random sampling techniques and the control group using purposive sampling techniques using matching methods. The purpose of this study was to determine the factors that influence the incidence of hypertension at the age of 20–54 years in the working area of the Wae Nakeng Health Center, West Manggarai Regency, in 2022. The sample size in this study was 114 samples, consisting of 57 case samples and 57 control samples. The results of this study showed that the factors that influenced the incidence of hypertension were coffee consumption (p = 0.045, OR = 2.827), alcohol consumption (p = 0.021, OR = 2.654), and smoking (p = 0.039, OR = 2.352), while factors that did not affect the incidence of hypertension were obesity (p = 0.651). People are expected to carry out health checks at the nearest health service facilities and can adopt a healthy lifestyle from an early age.